'Autonomous Functions of All Countries, Unite! You Have Nothing to Lose but Your Economic Anomie!' Emile Durkheim's Libertarian Socialist Critique. (September 2013) - Dawson, Matt
Scholars analysing Durkheim's relation to socialism have generally focused on whether Durkheim was personally a socialist and/or his discussion of socialism as a 'social fact'. This article focuses on whether Durkheim had a socialist theory. I will highlight how Durkheim's normative and socialist political sociology aimed its critique at: the dominance of the market economy; economic polarization; class conflict; the 'capitalist state'; and the impossibility of universal individual realization without radical economic change. From here Durkheim's framework for an alternative political society will be outlined. This alternative, with its advocacy of political organization in 'corporations', can be located within a tradition of 'libertarian' socialism found most prominently in the work of the early 20th-century English social theorist, G.D.H. Cole. It will be argued Durkheim offers a powerful explanation for the continued dominance of neoliberal ideas 'after the crash' and the resulting 'Occupy' protests.